Course design and development: Focus on student learning experience - Koomsap, Pisut (2019)
Learning is not an outcome and, as a process, is more than just taking classes. It is a transformation journey a student walks through, and experiences picked up along the journey contribute gradually to student competence development. Competence, what companies are looking for from graduates, cannot be handed directly and will not be built unless the learning process is properly designed, developed and executed. This research work aims to present a process for course design and development, focused on embedding learning experience into a course. Bloom's Taxonomy is utilized for identifying learning outcomes. Kolb's Experiential Learning Cycle is introduced for planning learning activities for ease of learning. Last, but not least, a recently developed LOVE model is applied for the selection of teaching and learning methods for offering a diversified learning experience. An existing project-based learning engineering postgraduate course on Product Design and Development is assessed to illustrate the proposed process for course design and development.